Biocatalytic synthesis of 2-fluoro-3-hydroxypropionic acid - Liu, Wei; Yuan, Shan; Jin, Miaomiao; Xian, Mo (Frontiers in Bioengineering and Biotechnology, 2022)
Fluorine has become an important element for the design of synthetic molecules for use in medicine, agriculture, and materials. The introduction of fluorine atoms into organic compound molecules can often give these compounds new functions and make them have better performance. Despite the many advantages provided by fluorine for tuning key molecular properties, it is rarely found in natural metabolism. We seek to expand the molecular space available for discovery through the development of new biosynthetic strategies that cross synthetic with natural compounds. Towards this goal, 2-fluoro-3-hydroxypropionic acid (2-F-3-HP) was first synthesized using E. coli coexpressing methylmalonyl CoA synthase (MatBrp), methylmalonyl CoA reductase (MCR) and malonate transmembrane protein (MadLM). The concentration of 2-F-3-HP reached 50.0 mg/L by whole-cell transformation after 24 h. 2-F-3-HP can be used as the substrate to synthesize other fluorides, such as poly (2-fluoro-3-hydroxypropionic acid) (FP3HP). Being entirely biocatalytic, our procedure provides considerable advantages in terms of environmental and safety impacts over reported chemical methods.